The Overtraining Syndrome in Athletes: The Challenge of Prevention
However, there is a limit to an athlete's capacity to endure and adapt to intense training. Once this threshold is crossed the athlete fails to adapt and performance declines. Ten to twenty percent of athletes who train intensively may fall prey to the overtraining syndrome, otherwise known as staleness (Kuipers, 1998; Krieder et al. 1997; Raglin & Wilson, in press). Athletes suffering from the overtraining syndrome are unable to train and perform to their capacity, and may experience a variety of other symptoms. The term overtraining itself is fraught with controversy and confusion. Some coaches and athletes contend that there is no limit beyond which training becomes counterproductive. The term also has been used inconsistently in the scientific literature with a variety of labels attached to this condition (O'Connor, 1997). For the purposes of this paper, the following definitions will be used. Overload--A planned, systematic and progressive increase in training with the goal of improving performance. Overreaching -- Unplanned, excessive overload with inadequate rest. Poor performance is observed in training and competition. Successful recovery should result from short-term (i.e., a few days up to one or two weeks) interventions. Overtraining Syndrome -- Untreated overreaching that results in chronic decreases in performance and impaired ability to train. Other problems may result and may require medical attention.